Pendampingan Pengelolaan Media Pembelajaran Interaktif untuk Meningkatkan Keterlibatan Siswa dalam Proses Pembelajaran - Muh. Alwi; Juhardi Juhardi; Risnashari Risnashari; Arifin Tahir; Kusmaladewi Kusmaladewi; Sitti Wahidah Masnani; Andi Agussalim (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service programme aims to improve teachers' understanding and skills in managing interactive learning media to increase student engagement in the learning process at SMAN 17 Lamuru, Bone Regency. Based on the results of the need assessment and situation analysis, it was found that the partners experienced several problems, including the lack of teacher understanding of information technology, the low ability of teachers to implement online learning, and the lack of knowledge about interactive learning media. This activity was attended by 25 participants and was carried out using various methods, such as lectures, questions and answers, discussions, brainstorming, demonstrations, and direct practice of online-based interactive learning media management. The materials provided were arranged in accordance with the objectives of the mentoring, and supported by instruments such as mentoring modules, observation sheets, participant satisfaction questionnaires, activity documentation, and other technical equipment. The main target of this programme is intangible, namely the realisation of mentoring participants who are able to understand the concept and create electronic modules for interactive learning.